2018
DOI: 10.1002/adom.201800109
|View full text |Cite
|
Sign up to set email alerts
|

Role of Localized States in Photoluminescence Dynamics of High Optical Gain CsPbBr3 Nanocrystals

Abstract: the visible to near-IR wavelengths of the electromagnetic spectrum. [9,10] Though organic-inorganic metal halides based perovskites can produce high photoluminescence (PL) yield, their instability makes it difficult for practical use. On the other side, all inorganic perovskite, e.g., cesium lead halides (CsPbX 3 ), based colloidal quantum dots attract much attention due to its very high PL yield (PLQY ≈ 90%), [11] narrow emission peak (enhanced color purity), low trap density, and reduced blinking [12] with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 47 publications
17
92
0
Order By: Relevance
“…For instance, Dey et al reported trap/defect‐assisted (from the localized states) ASE (from the localized states) in CsPbBr 3 NCs with a value of optical gain coefficient (51 cm −1 ) and a loss coefficient (15 cm −1 ). The NCs possess an ASE threshold of 5.8 µJ cm −2 pumped sub‐nanosecond (840 ps) excitation pulse width, this threshold value is comparable to many of the polyfluorene‐based waveguide …”
Section: Fundamentals In Perovskite‐based Lasersmentioning
confidence: 89%
See 2 more Smart Citations
“…For instance, Dey et al reported trap/defect‐assisted (from the localized states) ASE (from the localized states) in CsPbBr 3 NCs with a value of optical gain coefficient (51 cm −1 ) and a loss coefficient (15 cm −1 ). The NCs possess an ASE threshold of 5.8 µJ cm −2 pumped sub‐nanosecond (840 ps) excitation pulse width, this threshold value is comparable to many of the polyfluorene‐based waveguide …”
Section: Fundamentals In Perovskite‐based Lasersmentioning
confidence: 89%
“…To relate the output light variation with excitation length to gain, the excited region of length ( L ) with SE occurs uniformly in the excited state. A straightforward calculation shows that if the net gain experienced by the light is g tot = g′ ‐α (cm −1 ), then the detected light intensity is given byI λ=AP0gtotλ []expgtotλL1where AP 0 indicates the SE proportional to excitation intensity, g tot is the optical gain of the waveguide, L is the excitation beam length, g ′ is the gain due to stimulated emission, and α is the optical loss . As pumping length is varied, the observation of an exponential increase in the emitted light intensity could be considered as a direct evidence of the existence of gain.…”
Section: Fundamentals In Perovskite‐based Lasersmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the rapid progress in perovskite ASE or lasing, the intrinsic instability of CsPbBr 3 upon attacks by ambient moisture is still a serious challenge and hindrance for their practical applications owing to the surface defect, surface long ligands and ionic migration behaviors . For example, their surface long ligands and low stability could result in nonradiative recombination of excitons and photoluminescence emission degradation .…”
Section: Introductionmentioning
confidence: 99%
“…In P4 and P4L samples the emission intensity then starts decreasing at ≈175 K, as shown in Figure S14 of the Supporting Information. The decrease of the emission intensity with increasing temperature due to temperature activated nonradiative process is commonly observed in many materials, including perovskite nanocrystals, although nanocrystals may exhibit slower thermal quenching compared to perovskite thin films and single crystals . However, in the P4L samples with TOPO after the change of the peak shape at ≈75 K (disappearance of weak shoulder corresponding to defect emission), the emission intensity stays constant, as shown in Figure f.…”
mentioning
confidence: 81%